Clinical supervision under pressure: a qualitative study amongst health care professionals working on the ICU during COVID-19 - Marjel van Dam; Hanneke van Hamersvelt; Lisette Schoonhoven; Reinier G. Hoff; Olle ten Cate; Marije P. Hennus (Medical Education Online, 2023)
ABSTRACTPurpose The unprecedented influx of patients in 2020 with COVID-19 to intensive care units (ICU) required redeployment of healthcare professionals without adequate previous ICU-training. In these extraordinary circumstances, pivotal elements of effective clinical supervision emerged. This study sets out to explore the nature, aspects and key features of supervision under highly demanding circumstances among certified and redeployed health-care professionals on COVID-19 ICUs.Materials and methods A prospective qualitative, single center, semi-structured interview study among healthcare professionals at COVID-19 ICUs at University Medical Center Utrecht, the Netherlands between July and December 2020. Interview data were analyzed using an inductive coding style.Results A total of 13 certified and 13 redeployed health'hcare professionals, including physicians, nurses, and operation room technicians participated. Seven themes were identified as essential for both certified (supervisors) and redeployed (trainees) personnel: an open attitude, observing boundaries, gauging coworkers’ capacities, being available, providing feedback, continuity in care and teams, and combining supervision with workload.Conclusions This study provides seven recommendations for both supervisors and trainees to help optimize clinical supervision. They align with the known five factors determining entrustment and supervision (trainee, supervisor, task, context, and relationship). To ensure good clinical supervision, be it either during normal circumstances or under pressure, efforts should primarily focus on factors that are within a supervisor or trainee’s span of control.MeSH Clinical supervision, interprofessional, COVID-19, Intensive Care